RANCANG BANGUN ALAT MONITORING CUACA AREA PESISIR PANTAI DESA PACUNG, KABUPATEN BULELENG - Teguh Imantara, K; Adna Shavira, Andin; Amrita, A A N; Shandyasa, I W (Program Studi Teknik Elektro UNUD, 2023)
The weather changes due to global warming can impede human activities. This weather uncertainty has the potential to hinder local fishermen's operations, necessitating an Internet of Things (IoT) based weather monitoring system with strong wind notifications. This system utilizes the Telegram application platform and Thinger.io website to provide up-to-date weather information to the fishermen. One of the challenges faced by the fishermen of Desa Pacung is weather uncertainty. To address this, an IoT-based weather monitoring system with strong wind notifications was developed. This system employs the WeMos D1 R2 development board as the data processor and incorporates weather sensors such as an anemometer, wind direction sensor, DHT22 sensor, BH1750 sensor, and BMP180 sensor. Testing was conducted to compare the data from the monitoring system with BMKG data and evaluate the strong wind notifications. During the weather monitoring system testing, a comparison was made between the data from the weather monitoring system and BMKG data. The average difference between the system's data and BMKG data, measured every 5 minutes over 2 hours, was found to be due to topographical differences. The compared parameters were wind speed, light intensity, temperature, and humidity, with average differences for each parameter being 0.79 m/s, 26.7 Klx, 1.2?, and 5.3% respectively. A questionnaire was distributed to assess the usefulness of the device based on the opinions of 30 respondents. The average utility rating of the device reached 90.5%, categorizing the Desa Pacung weather monitoring prototype as highly suitable. The IoT-based weather monitoring system with strong wind notifications provides a solution for the fishermen of Desa Pacung in facing weather uncertainty.